The influence of VKORC1 polymorphisms on warfarin doses in thai patients with deep vein thrombosis - Nuttawut Sermsathanasawadi (2018)
© 2015, Medical Association of Thailand. All rights reserved. Background: Polymorphisms in cytochrome P450 2C9 and vitamin K epoxide reductase complex, subunit 1 genes (CYP2C9 and VKORC1, respectively) were previously shown to affect the warfarin dose required in anticoagulant therapy of deep vein thrombosis (DVT). However, little is known about the role of these genetic variants in the Thai population. Objective: To identify the effect of CYP2C9 and VKORC1 genetic variants on warfarin dosage in the Thai population with DVT. Material and Method: Genotyping of CYP2C9 (*2 and *3) and VKORC1 promoter (-1639G>A) variants were carried out in 97 Thai DVT patients receiving constant warfarin therapy and with a stable international normalized ratio using real-time PCR assays. Results: VKORC1 AA, GA, and GG genotype frequencies were found to be 49.5%, 46.4%, and 4.1%, respectively, while those of CYP2C9 genotypes were 88.7% for *1/*1 and 11.3% for *1/*3. The CYP2C9*2 variant was not present in the patients studied. The mean daily warfarin dose required to maintain a therapeutic INR differed significantly according to VKORC1 genotype, with 3.6 mg/day required for AA, 4.7 mg/day for GA, and 7.4 mg/day for GG (p-value <0.001). The CYP2C9 genotype did not significantly affect the warfarin dosage requirement (p-value = 0.29). Conclusion: These findings underline the impact of VKORC1 genotypes on the wide variation in warfarin maintenance dosing in Thai patients with DVT.